Analisa Perbandingan Hasil Pengelasan GTAW dan SMAW pada Pipa A36 dengan Metode Uji Radiografi - Muhammad Zulfikar; Maryadi Maryadi; Arifiansah Arifiansah; Tugiman Fahrudin (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the welding results between two commonly used methods, namely Gas Tungsten Arc Welding (GTAW) and Shielded Metal Arc Welding (SMAW), using radiographic testing methods. Welding is an important process in industry that affects the quality and strength of metal joints. In this study, we will examine the quality of welding results from both methods through radiographic testing, which serves to detect defects in welded joints. The GTAW method is known for its cleaner results and minimizes defects, while SMAW is often used because of its convenience and lower cost. The welding process is a crucial factor in ensuring the durability and performance of metal structures, and selecting the right welding method is essential for specific industrial applications. This study will compare the two methods based on the results of radiographic and tensile tests, evaluating factors such as weld strength, defect occurrence, and structural integrity. The analysis will also examine the advantages and disadvantages of each method in terms of weld quality, cost-effectiveness, and practical applications in different industries. It is hoped that the results of this study can provide deeper insights into the selection of the right welding method for industrial applications, as well as contribute to the development of welding technology. Furthermore, the findings will support improvements in quality control and provide a scientific basis for future welding practices in various manufacturing sectors.